2018
DOI: 10.1016/j.jsps.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a score to identify inpatients at risk of a drug-related problem during a 4-year period

Abstract: This value is higher than those reported in other studies describing validation of risk scores. The score showed good capacity to identify those patients at higher risk of DRP in a much larger sample of inpatients than previously described in the literature. This tool allows optimization of drug therapy monitoring in admitted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 55 publications
(89 reference statements)
4
30
0
1
Order By: Relevance
“…The prevalence of multimorbidity has been found to be 65%–80% in elderly populations 67. In correspondence with other studies, patients who possessed comorbid diseases had a higher risk of encountering DRPs 68. Adverse reactions, drug-use problems, and drug interactions were shown to be significantly associated with DRPs in this study, which is supported by a few others 69,70.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of multimorbidity has been found to be 65%–80% in elderly populations 67. In correspondence with other studies, patients who possessed comorbid diseases had a higher risk of encountering DRPs 68. Adverse reactions, drug-use problems, and drug interactions were shown to be significantly associated with DRPs in this study, which is supported by a few others 69,70.…”
Section: Discussionsupporting
confidence: 86%
“…They identified several independent risk factors of one or more DRP, namely age, Charlson's Comorbidity index, polypharmacy, several diagnostic categories (circulatory, digestive, musculoskeletal and connective, kidney and urinary tract) and drugs in several ATC classification classes (cardiovascular system drugs, systemic hormones, systemic antiinfectives, sensory organs agents, and various). The study included an initial validation of the identified predictor variables in 4058 subsequent admissions, reporting an area under the ROC curve of 0.78, with a second validation [27] being published later, based on retrospective cohort of 52,987 patients from the same hospital observed over 4 years, reporting an area under the ROC curve of 0.75. Our study adds to the knowledge base of risk factors of DRP in hospitalized patients by corroborating some of the results of the Urbina study.…”
Section: Plos Onementioning
confidence: 99%
“…Risk factors for DRP have been specifically studied in elderly populations [23], patients from medical specialties such as cardiology [24,25] and paediatrics [26]. To the best of our knowledge, there has been a single report in the literature investigating risk factors and developing a risk score for DRP in adult patients at hospital admission in general wards, the study by Urbina et al [13], with a subsequent validation study by Ferrández et al [27]. A 2015 study suggested a set of risk factors, but they were selected on the basis of expert opinions [28].…”
Section: Introductionmentioning
confidence: 99%
“…Através da metodologia DELPHI foram definidas 10 recomendações voltadas à utilização segura de insulina dentro de unidades de saúde e que o estabelecimento de protocolos institucionais são primordiais para promover a segurança do uso do medicamento. Ferrández et al (2018), realizaram um estudo para validar um score de pontuação para identificar pacientes de risco quanto a utilização de medicamentos. Os critérios de risco adotados foram: idade acima de 60 anos, número de comorbidades, polifarmácia, prescrição contendo medicamentos de alta vigilância e determinadas classes de medicamentos.…”
Section: Qualidade E Gestão De Processosunclassified